Discovery of a Novel Template, 7-Substituted 7-Deaza-4'-Thioadenosine Derivatives as Multi-Kinase Inhibitors - Karishma K. Mashelkar; Woong Sub Byun; Hyejin Ko; Kisu Sung; Sushil K. Tripathi; Seungchan An; Yun A Yum; Jee Youn Kwon; Minjae Kim; Gibae Kim; Eun-Ji Kwon; Hyuk Woo Lee; et al. (MDPI AG, 2021)
The development of anticancer drugs remains challenging owing to the potential for drug resistance. The simultaneous inhibition of multiple targets involved in cancer could overcome resistance, and these agents would exhibit higher potency than single-target inhibitors. Protein kinases represent a promising target for the development of anticancer agents. As most multi-kinase inhibitors are heterocycles occupying only the hinge and hydrophobic region in the ATP binding site, we aimed to design multi-kinase inhibitors that would occupy the ribose pocket, along with the hinge and hydrophobic region, based on ATP-kinase interactions. Herein, we report the discovery of a novel 4'-thionucleoside template as a multi-kinase inhibitor with potent anticancer activity. The in vitro evaluation revealed a lead 1g (7-acetylene-7-deaza-4'-thioadenosine) with potent anticancer activity, and marked inhibition of TRKA, CK1δ, and DYRK1A/1B kinases in the kinome scan assay. We believe that these findings will pave the way for developing anticancer drugs.